Polo-like kinase (PLK) 5, a new member of the PLK family, serves as a biomarker to indicate anabatic tumor burden and poor prognosis for resectable non-small cell lung cancer - Wang, Kaichao; Shen, Shaohui; Dong, Liyuan; Fang, Qinmo; Hou, Xinlei; Shi, Xueliang (Frontiers in Surgery, 2023)
Objective: A review argues that polo-like kinase 5 (PLK5) may be linked to unfavorable prognosis in non-small cell lung cancer (NSCLC) patients, which contradicts the discoveries from The Human Protein Atlas database (derived from TCGA analysis). This study intended to comprehensively confirm the association of PLK5 with clinical characteristics and prognosis in NSCLC patients. Methods: This two-center, retrospective, cohort study enrolled 210 NSCLC patients receiving surgical resection. PLK5 protein and mRNA were detected by immunohistochemistry and RT‒qPCR in tumor and nontumor tissues. Moreover, RNA FPKM data for 994 lung cancer patients were obtained from The Human Protein Atlas database. Results: PLK5 protein was decreased in tumor tissue compared to nontumor tissue (P<0.001). Additionally, decreased PLK5 protein was linked with increased pathological grade (P=0.002), lymph node metastasis presence (P=0.001), elevated tumor-node-metastasis (TNM) stage (P=0.003), and abnormal cancer antigen 125 (CA125) (P=0.002). Meanwhile, low PLK5 protein was correlated with shortened disease-free survival (DFS) (P=0.007) and overall survival (OS) (P=0.038); further multivariable Cox regression analysis revealed that low PLK5 protein independently predicted unfavorable DFS (hazard ratio=0.573, P=0.022). PLK5 mRNA was reduced in tumor tissue compared with nontumor tissue (P<0.001); its decline was linked with enhanced pathological grade (P=0.034), climbed TNM stage (P=0.032), and abnormal CA125 (P=0.002). Furthermore, low PLK5 mRNA was correlated with unfavorable DFS (P=0.046). The Human Protein Atlas database also disclosed the link between low PLK5 mRNA and worse OS (P=0.046). Conclusion: A PLK5 decrement reflects anabatic tumor burden and poor prognosis in NSCLC patients.